Resource Misallocation in European Firms: The Role of Constraints, Firm Characteristics and Managerial Decisions - Yuriy Gorodnichenko; Debora Revoltella; Jan Svejnar; Christoph T. Weiss (Institute of Labor Economics (IZA), 2018)
Using a new survey, we show that the dispersion of marginal products across firms in the European Union is about twice as large as that in the United States. Reducing it to the US level would increase EU GDP by more than 30 percent. Alternatively, removing barriers between industries and countries would raise EU GDP by at least 25 percent. Firm characteristics, such as demographics, quality of inputs, utilization of resources, and dynamic adjustment of inputs, are predictors of the marginal products of capital and labor. We emphasize that some firm characteristics may reflect compensating differentials rather than constraints and the effect of constraints on the dispersion of marginal products may hence be smaller than has been assumed in the literature. We also show that cross-country differences in the dispersion of marginal products are more due to differences in how the business, institutional and policy environment translates firm characteristics into outcomes than to the differences in firm characteristics per se.
Keywords: O12; O47; O52; D22; D24; 330; marginal products; resource allocation; firm-specific factors; economic growth